PENGARUH PROGRAM K3 DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. APAC INTI CORPORA BAWEN (STUDI KASUS PADA KARYAWAN BAGIAN WINDING DEPARTEMEN SPINNING 2) - Sihotang, Rita Mustika; Hermani, Agus; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
This research is motivated that part which plays an important role in achieving the goal of a company is the human resources, namely the employee. Companies can develop better if followed by high employee work productivity. PT. Apac Inti Corpora Bawen has a target to increase employee productivity. However, the production employee winding section spinning department 2 PT. Apac Inti Corpora Bawen in 2013 and 2014 did not meet its targets. The purpose of this study was to determine the influence of HSE programme and compensation either simultaneously or partially on employee productivity spinning department winding section 2. This type of research is